2018
DOI: 10.1111/acer.13594
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Opioid Use, Co‐Use, and Chronic Pain in the Context of the Opioid Epidemic: A Critical Review

Abstract: The dramatic increase in opioid misuse, opioid use disorder (OUD), and opioid-related overdose deaths in the United States has led to public outcry, policy statements, and funding initiatives. Meanwhile, alcohol misuse and alcohol use disorder (AUD) are a highly prevalent public health problem associated with considerable individual and societal costs. This study provides a critical review of alcohol and opioid misuse, including issues of prevalence, morbidity, and societal costs. We also review research on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(100 citation statements)
references
References 132 publications
(159 reference statements)
6
94
0
Order By: Relevance
“…In contrast, there is evidence for a positive association between excessive alcohol consumption and increased pain, although evidence for this relation has been more mixed. A prospective study of older adults has found that problem drinkers experienced higher levels of pain and pain interference (Brennan et al, ), and Witkiewitz and Vowles’s () review documented that 16 to 25% of chronic pain patients in treatment reported a history of heavy alcohol use or AUD. In contrast, population‐based and clinical studies have linked heavy drinking to reduced pain and pain‐related functioning among patients with chronic pain disorders (e.g., Kim et al, ; MacFarlane et al, ).…”
Section: Associations Of Alcohol and Pain‐related Outcomesmentioning
confidence: 99%
“…In contrast, there is evidence for a positive association between excessive alcohol consumption and increased pain, although evidence for this relation has been more mixed. A prospective study of older adults has found that problem drinkers experienced higher levels of pain and pain interference (Brennan et al, ), and Witkiewitz and Vowles’s () review documented that 16 to 25% of chronic pain patients in treatment reported a history of heavy alcohol use or AUD. In contrast, population‐based and clinical studies have linked heavy drinking to reduced pain and pain‐related functioning among patients with chronic pain disorders (e.g., Kim et al, ; MacFarlane et al, ).…”
Section: Associations Of Alcohol and Pain‐related Outcomesmentioning
confidence: 99%
“…Alcohol use disorders affect an estimated 15.8 million people, an estimated 1.9 million people abuse or are dependent on prescription opioids and 323,000 are dependent on heroin (Center for Behavioral Health Statistics and Quality, 2015; Substance Abuse and Mental Health Services Administration, 2014). OAUDs also frequently co-occur with each other and with other substance use disorders (SUDs) (Grant et al, 2015), making them more challenging to treat and more likely to be persistent and severe (McCabe and West, 2017; Moss et al, 2015; Upah et al, 2015; Witkiewitz and Vowles, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…The synergism of negative health outcomes occurring with the consumption of opioids with other agents has become commonplace as well. Witkiewitz and Vowles have pointed to heavy consumption of alcohol accompanying opioid misuse had led to a public health crisis with deleterious impacts upon patient morbidity and mortality. They also suggest that concurrent abuse of alcohol coupled with opioid abuse co‐occurs along with chronic pain and, in fact, is under‐researched .…”
mentioning
confidence: 99%
“…Witkiewitz and Vowles have pointed to heavy consumption of alcohol accompanying opioid misuse had led to a public health crisis with deleterious impacts upon patient morbidity and mortality. They also suggest that concurrent abuse of alcohol coupled with opioid abuse co‐occurs along with chronic pain and, in fact, is under‐researched . Australian researchers, Degenhardt and Hall, suggest that level of illicit drug use, including opioids, occurs more frequently in high‐income countries or in countries geographically close to drug‐producing countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation